EW91-01: New multichannel seismic results from Bransfield Strait, Antarctica - Barker, DHN; Austin, JA Jr (Antarctic journal of the United States, 1993)
A joint cruise by the University of Texas Institute for Geophysics and the Lamont-Doherty Earth Observatory in February and March 1991 acquired deep-penetration multichannel seismic reflection data in Bransfield Strait and offshore the South Shetland "arc" as part of cruise EW91-01 of the Lamont-Doherty research vessel Maurice Ewing. These data give the best existing opportunity for imaging the deep structure of the basin. The data comprise more than 2,000 kilometers of reflection profiles. Also acquired were Hydrosweep multibeam bathymetry, gravity, and magnetic data.